2018
DOI: 10.1080/15476278.2018.1501136
|View full text |Cite
|
Sign up to set email alerts
|

Serum- and albumin-free cryopreservation of endothelial monolayers with a new solution

Abstract: Cryopreservation is the only long-term storage option for the storage of vessels and vascular constructs. However, endothelial barrier function is almost completely lost after cryopreservation in most established cryopreservation solutions. We here aimed to improve endothelial function after cryopreservation using the 2D-model of porcine aortic endothelial cell monolayers. The monolayers were cryopreserved in cell culture medium or cold storage solutions based on the 4°C vascular preservation solution TiProtec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…Compared to cryopreservation of suspended cells, protocols for adherent cell monolayers are significantly lacking. To date, there have been few studies on the slow-freezing (nonvitrified) cryopreservation of monolayered cells. 3-D cell cultures such as spheroids or organoids present even more complexity, such as the significant impact of spheroid size on recovery (large <40% recovery vs small <70%) along with required equilibration times, and hence result in lower cell yields post-thaw. This is clearly observed with human embryonic kidney cells, where 3-D cryopreservation led to recovery of only 36%, and improved methods are obviously required.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to cryopreservation of suspended cells, protocols for adherent cell monolayers are significantly lacking. To date, there have been few studies on the slow-freezing (nonvitrified) cryopreservation of monolayered cells. 3-D cell cultures such as spheroids or organoids present even more complexity, such as the significant impact of spheroid size on recovery (large <40% recovery vs small <70%) along with required equilibration times, and hence result in lower cell yields post-thaw. This is clearly observed with human embryonic kidney cells, where 3-D cryopreservation led to recovery of only 36%, and improved methods are obviously required.…”
Section: Introductionmentioning
confidence: 99%
“…The above results suggested that the intra/extracellular localization of AFPIII was not sufficient for enhancing mammalian cell cryopreservation in suspension freezing. While this is the most standard cell cryopreservation format, there is a real need to develop technologies and methods for 2- and 3-D cell models, for tissue storage and organ-on-a-chip applications. The monolayer freezing protocol is illustrated in Figure A. A549 monolayers were frozen in DMSO alone, or with AFPIII (0.8 mg·mL –1 ), AFPIII (0.8 mg·mL –1 ) plus Pep-1 (0.5 mg·mL –1 )), or Pep-1 alone (0.5 mg·mL –1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cryopreservation of cells in monolayer format is currently being investigated as a means to supply cells which can be readily used and do not experience extensive “phenotypic drift” due to time-consuming laboratory processes, such as inoculation and propagation, from frozen vials. Successful monolayer cryopreservation of cells would be revolutionary in minimizing batch-to-batch variation and for the development of 2- and 3-D cell models, tissue storage, viral diagnostics, and organ-on-a-chip applications. However, the current standard (DMSO) approaches used in suspension freezing are not translatable to monolayer freezing, with evidence suggesting that cells within a 2- and 3-D network (monolayers and spheroids/organoids) experience different modes of cryoinjury. , Thus, development of novel cryoprotectants tailored toward the format of cryopreservation and to replace or reduce DMSO content is pivotal for the future development of cell-based therapies and diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…In that work, the authors showed that 5% DMSO and 5% HES in the presence of 90% fetal calf serum resulted in only about 50% viability post-thaw [ 85 ]. Similarly, using an improved media formulation (TiProtec, which proved favourable for cold storage of blood vessels) in the cryopreservation of porcine aortic endothelial cell monolayers enhanced mitochondrial integrity and yielded only 50% viable cells [ 86 ]. Addition of antifreeze proteins to 10% DMSO and slow cooling of A549 epithelial cell line monolayers improved post-thaw recovery from 25% to 60% [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%